ONLINE RUQYAH AS A SOURCE OF NON FORMAL RELIGIOUS LEARNING: A SOSIOEDUCATIONAL ANALYSIS - Slamet Kartono; Ika Septiana; Harjito (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The rapid expansion of digital media has transformed religious communication, enabling spiritual guidance to be accessed beyond formal educational settings. This study examines online ruqyah as a source of nonformal religious learning and explores its socioeducational implications for participants’ religious literacy. Using a descriptive qualitative approach within an interpretative paradigm, the research analyzes eleven ruqyah sessions conducted by Jam’iyyah Ruqyah Ahlussunah Waljamaah (JRA) on the Ruqyah Aswaja TV YouTube channel. Data were collected through documentation and non-participant observation, followed by verbatim transcription and thematic analysis. The findings indicate that online ruqyah sessions function as multidimensional learning environments where religious knowledge, practices, and values are transmitted through ritual-based interaction mediated by digital technology. Participants develop theological understanding, practical religious skills, emotional engagement, and reflective awareness through guided participation and repeated exposure. The accessibility of YouTube supports voluntary and self-directed learning while fostering virtual religious communities. From a socioeducational perspective, online ruqyah integrates spiritual healing with religious education, demonstrating the potential of digital platforms to enhance religious literacy and spiritual well-being in contemporary Muslim societies.